2015
DOI: 10.1016/j.diii.2013.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of acute pancreatitis and its complications. Part 1: Acute pancreatitis

Abstract: Acute pancreatitis is an acute inflammatory disease of the pancreas that may also involve surrounding tissues or remote organs. The Atlanta classification of acute pancreatitis was introduced in 1992 and divides patients into mild and severe groups based on clinical and biochemical criteria. Recently, the terminology and classification scheme proposed at the initial Atlanta Symposium have been reviewed and a new consensus statement has been proposed by the Acute Pancreatitis Classification Working Group. Gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
51
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 45 publications
0
51
0
3
Order By: Relevance
“…US is the basic imaging modality in most centers to confirm the diagnosis of AP and ruling out of other causes of acute abdomen [45], yet, sometimes of limited value [44]. US shows focally or diffusely enlarged hypoechoic pancreatic gland.…”
Section: Prognosismentioning
confidence: 99%
“…US is the basic imaging modality in most centers to confirm the diagnosis of AP and ruling out of other causes of acute abdomen [45], yet, sometimes of limited value [44]. US shows focally or diffusely enlarged hypoechoic pancreatic gland.…”
Section: Prognosismentioning
confidence: 99%
“…Dans ce numéro de formation médicale continue, Türkvatan et al présentent un excellent aperçu des aspects tomodensitométriques (TDM) variés de la pancréatite aiguë (PA) et de ses complications potentielles [1,2]. Il n'y a actuellement aucun doute sur le fait que la TDM est l'examen d'imagerie clé dans le domaine de la PA. Ceci est conforté par une importante quantité de données présentes dans la littéra-ture médicale scientifique [3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Pancréatite Aiguë : Le Scanner N'attend Pasunclassified
“…Dans leurs articles, Türkvatan et al ont abordé le rôle de l'IRM dans le diagnostic de PA [1,2]. Jusqu'à présent, plusieurs études ont montré que l'IRM est un outil utile pour le diagnostic de PA et est équivalente [19,20] ou surpasse même la TDM [8] pour évaluer la gravité de la maladie.…”
Section: Pancréatite Aiguë : Le Scanner N'attend Pasunclassified
“…In this issue of Diagnostic and Interventional Imaging, Türkvatan and colleagues present a nice overview of the computed tomography (CT) features of acute pancreatitis (AP) and its potential complications [1,2]. There is currently no doubt upon the fact that CT is the key imaging test in the area of AP.…”
mentioning
confidence: 99%
“…In their papers, Türkvatan et al have addressed the role of MR imaging for the diagnosis of AP [1,2]. So far, several studies have showed that MR imaging is a useful tool for the diagnosis of AP and is equivalent to [19,20] or even surpasses CT [8] for evaluating the severity of the disease.…”
mentioning
confidence: 99%